2017
DOI: 10.21767/2171-6625.1000203
|View full text |Cite
|
Sign up to set email alerts
|

Basic activity of Neurons in the dark during Somnolence induced by Anesthesia

Abstract: Citation: Etindele Sosso FA, Hito MG, Bern SS (2017) Basic activity of neurons in the dark during somnolence induced by anesthesia. J Neurol Neurosci 8:3. AbstractAim:The first experience modulates the network of integration and memory in the sleeping cortex. Depending on the characteristics of this initial stimulation, the brain adjusts his electrical activity to respond during wake or sleep. This adjustment is different for every sub type of neurons and are influenced by the information drove by stimuli. Pyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…This short-term plasticity process occurs almost immediately after stimulus presentation, within 1 minute; and most of neurons displayed shifts of peaks of oriented tuning curves. In addition to orientation in many animals, similar modifications of optimal stimuli were reported for direction, speed, spatial frequency [9][10][11][12].…”
Section: Introductionsupporting
confidence: 55%
“…This short-term plasticity process occurs almost immediately after stimulus presentation, within 1 minute; and most of neurons displayed shifts of peaks of oriented tuning curves. In addition to orientation in many animals, similar modifications of optimal stimuli were reported for direction, speed, spatial frequency [9][10][11][12].…”
Section: Introductionsupporting
confidence: 55%
“…This complex combination of environmental and psychological stress may contribute to developing neurological dysfunctions, such as sleep disorders. Although some sleep disorders are consequences of cortical imbalances 6 , including insomnia and restless leg syndrome, lifestyle can influence their incidence considerably [7][8][9][10] . New technologies are part of this lifestyle, including the internet and gaming, which may affect mental health and may lead to the development of addictive behavior particularly in young individuals [11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a negative correlation was found between psychopathological symptoms (i.e., anxiety, depression and stress) and the development of behavioral problems, such as decreases in psychological wellbeing 5,10,28 . It has also been reported that the presence of or exposure to light can disturb the circadian rhythm, the melatonin cycle and cerebral plasticity 6 . To fall asleep, inhibition increases, while excitation decreases.…”
Section: Introductionmentioning
confidence: 99%
“…behavioural insomnia, idiopathic insomnia, or insomnia related to a mental disorder), sleep disorders often have their origins in hygiene of inappropriate life to get a quality sleep and adequate duration. It is strongly correlated with living conditions that are dependent on or influenced by environmental psychobiological risk factors; through its indicators of socio-economic status and environmental stress [9][10][11][12][13][14][15][16][17][18]. Many studies have established a negative relationship between the presence of predisposing factors to metabolic diseases (such as stroke or cardiovascular disease) and cognitive impairment, accompanied by decreased attention, decreased reflexes engines and the ability to perform multiple tasks.…”
Section: Introductionmentioning
confidence: 99%